2022
DOI: 10.4103/jisppd.jisppd_224_22
|View full text |Cite
|
Sign up to set email alerts
|

Nanosilver fluoride as a caries arresting agent in children

Abstract: Background: Dental caries is one of the most common concerns in oral health of children. Arresting these lesions is a treatment which is gaining momentum as against conventional restorative approaches. Aim: The aim is to evaluate the efficacy of nanosilver fluoride (NSF) as a caries arresting agent in primary teeth or first permanent molars in children. Design: The protocol for the systematic review has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…9. Another systematic review and meta-analysis in 2022 by Choubey Shikha et al found that NSF is an effective means for caries arrest in primary teeth (38).…”
Section: Evidence Based Studies On the Efficiency Of Nsfmentioning
confidence: 99%
“…9. Another systematic review and meta-analysis in 2022 by Choubey Shikha et al found that NSF is an effective means for caries arrest in primary teeth (38).…”
Section: Evidence Based Studies On the Efficiency Of Nsfmentioning
confidence: 99%
“…This damages the cell membrane and interferes with DNA replication leading to bacterial cell death [ 22 ]. Evidence showed the anti-caries property and better efficacy of NSF than the control in ECC arrest [ 19 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%